CONFLICTOS EN LAS EMPRESAS. ESTUDIO DE UN CASO - Raquel Mirás (European Scientific Journal, ESJ, 2015)
This work deals with frequent conflicts between managers and subordinates. It does not clarify the objectives and functions of each of them and the context of power between them. An approach to the processes of communication and interpersonal transactions where they can generate conflicts, real or psychological objectives within the company was made. Instruments of Transactional Analysis, applied to organizational coaching for conflict resolution were also presented. For Carolina, architect was presented as an example of its application.